Fast and Furious: Podemos' Quest for Power in Multi-level Spain. Issue 4 (1st October 2016) - Rodríguez-Teruel, Juan; Barrio, Astrid; Barberà, Oscar
Abstract: After a stunning breakthrough in the 2014 European election, Podemos became the third largest parliamentary party in Spain in the 2016 general election and achieved representation in all regions. This article examines how Podemos has adapted to the opportunities and dilemmas posed by Spain's multi-level setting in several ways: its formation in early 2014 and its evolution since; its ideological principles and policy menu; its organisation; and its political strategies and electoral alliances. The hypotheses test the effects of adaptation to multi-level competition on the party electorate. The findings indicate the positive effect of support for more decentralisation on the likelihood of voting for Podemos, but also how this effect is territorially differentiated and could affect the party's cohesion and internal debate.